From figures to facts: Making sense of socioeconomic surveys in the Democratic Republic of the Congo (DRC) - Marivoet, Wim; De Herdt, Tom (2017)
Over the last decades, both donor organizations and the national government have invested heavily in administering national-level surveys in the DRC. These survey results have been used in planning exercises (e.g. to elaborate the Poverty Reduction Strategy Papers) and in evaluation exercises (e.g. to decide on the country’s debt relief), but the quality of these data is highly contentious as some basic demographic information on the DRC is simply unknown. This policy brief first presents the issue and illustrates its direct implications before we present a discussion of possible solutions, also for the short-run.